2013
DOI: 10.4236/jep.2013.410121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Flaring on Soil and Cassava Productivity in Ebedei, Ukwuani Local Government Area, Delta State, Nigeria

Abstract: The threat to human, fauna and flora life posed by pollution due to gas flaring cannot be over-emphasized. Gas flared often resulted in some environmental degradation, one of such influence is soil pollution and poor crop yield. This study examined the effect of gas flaring on soil and cassava productivity in Ebedei, Ukwuani LGA, Delta State. For the purpose of data collection, five (5) experimental sites were systematically selected around the flare site in Ebedei and a control site at Obiaruku. Soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 7 publications
5
16
2
Order By: Relevance
“…The radiation profile decreased with increasing distance from the flare. This agrees with the work of [2] that the radiation intensity increased with increasing distance to the flare. This increase in radiation intensity and environmental temperature are implicated for the poor performance of crops around the flare site.…”
Section: Effect Of Time and Seasonal Variation On Radiation Profilesupporting
confidence: 92%
See 2 more Smart Citations
“…The radiation profile decreased with increasing distance from the flare. This agrees with the work of [2] that the radiation intensity increased with increasing distance to the flare. This increase in radiation intensity and environmental temperature are implicated for the poor performance of crops around the flare site.…”
Section: Effect Of Time and Seasonal Variation On Radiation Profilesupporting
confidence: 92%
“…According to [2] that radiation intensity increased with decreasing distance to the flare. The study also showed that as the distance is decreasing towards the flare site, pH is also decreasing from 5.50 (at 1000 -2000 m) to 4.94 (at 0-150 m).…”
Section: Effect Of Flare Distance On the Physicochemical Properties Of Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…It involves the controlled burning of the gas, as a common practice in oil/gas exploration, production and processing operations (EPA, 2014), especially in Nigeria (Oni & Oyewo, 2011). Therefore, gas flaring is the wasteful burning of natural gas during crude oil processing by the oil industry (Banerjee, 1995;Atuma & Ojeh, 2013;Abdulkadir et al, 2013). This gas is burnt off either through ground (horizontal) flare (Plate 1) or vertical (elevated) (Plate 2) (Nnimmo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gas faring, as a common practice in the oil production process, is an incomplete combustion of surplus hydrocarbon congregated in an oil or gas production gas flare site (Atuma and Ojeh, 2013). Although the international community, in trying to combat the menace of global warming and other attendant effects of air pollution, proposes a complete cessation of flaring activities, there are still areas around the world were significant gas flaring activities are still being observed.…”
Section: Introductionmentioning
confidence: 99%